Phil Fieber Oral History Interview - (:unkn) unknown (My University, 2012)
Phil Fieber is the head of Eau Claire Parks and Recreation. He was the radio voice of the Eau Claire Braves for five years, from 1955-1960. He was instrumental in procuring the Hank Aaron statue for Carson Park. Mr. Fieber discusses the impact of baseball on the Eau Claire community and has worked with Carson Park and local little league teams.